2014
DOI: 10.1589/jpts.26.1875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Open and Closed Kinetic Chain Exercises in Rehabilitation Following Anterior Cruciate Ligament Reconstruction

Abstract: [Purpose] To compare outcomes of anterior cruciate ligament (ACL) reconstruction after open kinetic chain (OKC) exercises and closed kinetic chain (CKC) exercises. [Subjects and Methods] The subjects comprised 11 female and 47 male patients who are randomly divided into two groups: which performed a CKC exercise program Group I and Group II which performed an OKC exercise program. Pain intensity was evaluated using visual analogue scale (VAS). Knee flexion was evaluated using a universal goniometer, and thigh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 18 publications
0
33
0
5
Order By: Relevance
“…They included the RCTs of Bynum et al ,64 Mikkelsen et al ,67 Morrissey et al 68 and Perry et al 69. The recent RCT of Uçar et al 70 found no differences between CKC and OKC exercises, but they investigated a group of patients after ACLR with a HS graft.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They included the RCTs of Bynum et al ,64 Mikkelsen et al ,67 Morrissey et al 68 and Perry et al 69. The recent RCT of Uçar et al 70 found no differences between CKC and OKC exercises, but they investigated a group of patients after ACLR with a HS graft.…”
Section: Resultsmentioning
confidence: 99%
“…The overall conclusions were as follows: Level 1 : CKC and OKC training can be used for regaining quadriceps strength 61 62 70

Level 2 : after ACLR, OKC exercises can be performed from week 4 postoperative in a restricted ROM of 90–45° 61 63 65 66

…”
Section: Resultsmentioning
confidence: 99%
“…A similar opinion concerning pain intensity in a postsurgical period in patients after the ACL reconstruction was expressed by Yabroudi et al, who revealed high usefulness of controlling postsurgical pain and oedema in a knee join area [33]. While assessing the value of exercises in open and closed kinematic chains after the ACL reconstruction, Ucar et al also applied the Visual Analogue Scale [37].…”
Section: Dyskusjamentioning
confidence: 82%
“…Podobną opinię o wartości pomiaru natężenia bólu w okresie pooperacyjnym u chorych po rekonstrukcji ACL wyrażają Yabroudi i wsp., którzy w swoim badaniu wykazali dużą przydatność kontrolowania po zabiegowego bólu i obrzęku okolicy stawu kolanowego [33]. Ucar i wsp., oceniając wartość ćwiczeń w otwartych i zamkniętych łańcuchach kinematycznych po rekonstrukcji ACL, również wykorzystywali wizualno-analogową skalę bólu VAS [37].…”
unclassified
“…En la siguiente fase se pueden realizar ejercicios de propiocepción con apoyo unipodal y se pueden ir complicando progresivamente al pedir al paciente que cierre los ojos. En la fase final se realizan todos los ejercicios de las fases anteriores pero añadiendo complicaciones a la realización del ejercicio, combinando distintas superficies y solicitando al paciente movimientos rápido y explosivos, pero sin perder el equilibrio (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Procedimientounclassified